IN VITRO INDUCTION OF CALLUS ON AGLAONEMA "BUTTERFLY" LEAVES WITH A COMBINATION OF 2,4-D AND BAP - Ardhika Ratri, Jessie; Ratnawati (Indonesian Journal of Bioscience (IJOBI), 2024)
This research aims to determine the effect of variations and the concentration level of 2,4-D in a medium containing BAP which gives the best for callus formation on Aglaonema Butterfly in vitro. This research is an experimental study using 2,4-D (ppm; 0.5 ppm; 1 ppm; 2 ppm; 4 ppm) and 1.2 ppm BAP. Explants were taken from young leaves of the 2nd and 3rd Aglaonema Butterfly from the shoots, with the size of the explants being 1 x 2 cm. The parameters observed were callus emergence time, the percentage of explants forming callus, the average callus size, the rate of surviving explants, and the level of explant browning. The variation of 2,4-D in a medium containing BAP affected the callus emergence time, the percentage of explants forming callus, and the average of Aglaonema Butterfly callus size. The best treatment was at a concentration 2 ppm 2,4-D + 1.2 ppm BAP concentration at 4 weeks after planting, with 50% of explants forming callus, the average callus size was 0.82 mm, live explants were 87.5%, and the lowest browning rates.